Recombinant Tropomyosin from the Pacific Oyster (Crassostrea gigas) for Better Diagnosis - Roni Nugraha; Thimo Ruethers; Aya C. Taki; Elecia B. Johnston; Shaymaviswanathan Karnaneedi; Sandip D. Kamath; Andreas L. Lopata (Foods, 2022)
The Pacific oyster is a commercially important mollusc and, in contrast to most other shellfish species, frequently consumed without prior heat treatment. Oysters are rich in many nutrients but can also cause food allergy. Knowledge of their allergens and cross-reactivity remains very limited. These limitations make an optimal diagnosis of oyster allergy difficult, in particular to the Pacific oyster (Crassostrea gigas), the most cultivated and consumed oyster species worldwide. This study aimed to characterise IgE sensitisation profiles of 21 oyster-sensitised patients to raw and heated Pacific oyster extract using immunoblotting and advanced mass spectrometry, and to assess the relevance of recombinant oyster allergen for improved diagnosis. Tropomyosin was identified as the major allergen recognised by IgE from 18 of 21 oyster-sensitised patients and has been registered with the WHO/IUIS as the first oyster allergen (Cra g 1). The IgE-binding capacity of oyster-sensitised patients’ IgE to purified natural and recombinant tropomyosin from oyster, prawn, and dust mite was compared using enzyme-linked immunosorbent assay. The degree of IgE binding varied between patients, indicating partial cross-sensitisation and/or co-sensitisation. Amino acid sequence alignment of tropomyosin from these three species revealed five regions that contain predicted IgE-binding epitopes, which are most likely responsible for this cross-reactivity. This study fully biochemically characterises the first and major oyster allergen Cra g 1 and demonstrates that the corresponding recombinant tropomyosin should be implemented in improved component-resolved diagnostics and guide future immunotherapy.